Pengaruh Bauran Pemasaran Terhadap Keputusan Menjadi Anggota di BMT Al-Ishlah Kota Jambi - Frissia Friszki Melati; Anzu Elvia Zahara; Muhammad Subhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine whether the marketing mix consisting of product, price, location, and promotion has a significant effect on the decision to become a member of BMT Al-Ishlah Jambi City. The method and type of research used is quantitative influence. The research was conducted at BMT Al-Ishlah Jambi City because it is easy to collect data and obtain research permits, support for academic research and a sufficient population of 564. The sampling method used was simple random sampling, so that 85 samples were obtained. The research instruments used documentation and questionnaires. The data processing and analysis methods used in this study include descriptive analysis, validity and reability tests, data analysis and hypotesis testing. The results showed that the product, location and promotion variables partially had No. significant effect on the decision to become a member of BMT Al-Ishlah Jambi City, while on the price variable partially had a positive and significant effect on the decision to become a member of BMT Al-Ishlah Jambi City. And simultaneously, the variables of product, price, location, and promotion affect the decision to become a member of BMT Al-Ishlah Jambi City.